Eine angelsächsische Riemenzunge aus Rieseby an der Schlei - Kurz, Jule (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
Due to a suspected Anglo-Saxon origin, the contextless detector find of a copper-aloy strap-end from Rieseby on the Schlei becomes a promising subject for further research: Did it really come from Britain? If so, what is its significance regarding the nature of the early medieval relationship between Britain and the Schlei? Has it been traded, stolen, bought…? !e first important step was a general typological, chronological and geographical classification. It was possible to assign the strap-end to the 9th century Trewhiddle- Style, subtype a, of southern British origin. This led to a search for further datable Anglo-Saxon objects found along the Schlei and – to find out about possible ways to and uses by their new owners – from Scandinavia in general. Concerning An glo-Saxon coins, only two stycas of the 9th century from the Schlei have been published so far. In terms of ornamented metal work, sporadic pieces of jewellery as well as eight Anglo-Saxon strap-ends from the relevant period appear among the finds of Füsing, Haithabu and Haitha- bu-South. Most interestingly, those could also be assigned to the Trewhiddle-Style. At this point of research, the number and nature of relevant finds make tradingconnections quite improbable. Supported by modifications on some of the objects and the fact that many of them are part of the costume, an interpretation as a souvenir or looted good, which was probably brought to the Schlei as the property of an individual in the context of Viking imperialism in Britain, seems realistic for the Rieseby strap-end.